Current Status and research hotspots in the field of full endoscopic spine surgery: A bibliometric analysis - Lin, Guang-Xun; Zhu, Ming-Tao; Kotheeranurak, Vit; Lyu, Pengfei; Chen, Chien-Min; Hu, Bao-Shan (Frontiers in Surgery, 2022)
Purpose: We aimed to comprehensively analyze the current status, hotspots, and trends in full endoscopic spine surgery (FESS) research using bibliometric analysis and knowledge domain mapping. Methods: The Web of Science database was used to screen FESS-related articles published between January 1, 1993 and June 10, 2022. The evaluation involved the following criteria: total number of articles; H-index; and contributions from countries/regions, institutions, journals, and authors. Results: A total of 1,064 articles were included. Since 2016, there have been a significant number of publications in the field of FESS. The country/region contributing the largest number of articles was China (37.8%), followed by South Korea (24%), the United States (16.1%), Japan (5.7%), and Germany (5.1%). South Korea (35) had the highest H-index, followed by the United States (27), China (22), Japan (21), and Germany (20). World Neurosurgery (15.7%) published the largest number of FESS-related articles. However, among the top 10 most cited articles, six were published in Spine. The author who contributed the most was S.H. Lee (5.4%), and the largest number of contributions in this field originated from Wooridul Spine Hospital (South Korea; 6.1%). Notably, six of the 10 most published authors in this field were from South Korea. Of the top five productive institutions, three were from South Korea. The keywords with the strongest citation bursts in the field of FESS were “lumbar spine,” “discectomy,” “interlaminar,” “surgical technique,” “follow-up,” “excision,” “thoracic spine,” and “endoscopic surgery.” The 10 clusters generated in this study were: “endoscopic discectomy” (#0), “thoracic myelopathy” (#1), “recurrent lumbar disc herniation” (#2), “low back pain” (#3), “cervical vertebrae” (#4), “lumbar spinal stenosis” (#5), “transforaminal lumbar interbody fusion” (#6), “radiation exposure” (#7), “management” (#8), and “lumbar spine” (#9). Conclusion: Global research on FESS is mostly concentrated in a few countries/regions and authors. South Korea has made the largest contribution to the field of FESS. Based on the most cited keyword bursts and clusters, the focus of FESS research was found to include its indications, management, and applications.